Temperature Effect on the Physical Properties of Enamel Paint Layer on Cement Plaster - Samiul Kaiser; Mohammad Salim Kaiser (Journal of Engineering Science, 2021)
The heating effect on the stability and visual colour of enamel paint on cement plaster is evaluated through light intensity ratio of three primary colours (RGB). The painted cement plaster is isochronally heated in an electric resistance furnace at different temperatures for one hour. The investigation of optical images reveals that the original colour of the paint layer on the plaster samples remains more or less unchanged up to heating at 100°C. However, thermal degradation of the samples becomes evident in colour when they are heated beyond 200°C and at 350°C the colour becomes already burned. The microstructural images of the samples at room temperature show fine and uniform grains. But at higher heating condition the microstructure of the colour sample is characterized by coarsening grain. The colour of the heated samples are then studied through tristimulus colour ‘L*’, ‘a*’ ‘b*’ and ‘E*’ values which were analyzed and evaluated in MATLAB software. The results show that after 200°C the hunter ‘L*’ value starts to decrease greatly up to 250°C. The hunter ‘a*’ value shows an increasing trend up to 100°C and then begins to decrease until 200°C. After 200°C the same increasing character is showed till 300°C. The change of hunter ‘b*’ value remains insignificant up to 100°C and shows decreasing trend between 100°C-250°C range and an increase after 250°C up to 300°C. It is graphically shown that the proportion of all three colours decreases with the increasing temperature. The overall change of colour ‘E*’ occurs with increasing heating temperature due to moisture releasing, chemical changes and thermal degradation simultaneously. The thickness of enamel paint layer comply the above degradation by showing the nature of decreasing trend.